PERSEPSI MAHASISWA STIKES PASAPUA AMBON TENTANG PEMBELAJARAN DARING - Amarlita, Dhamas Mega; Ruhukail, Novita L. (Al-Alam: Islamic Natural Science Education Journal, 2023)
The social distancing in Indonesia gives a large impact in university’s teaching and learning processes. 100% of them are done by online. This online process is considered as the most effective way to hold the learning process without gathering any crowded. This also applied in STIKes Pasapua of Ambon. This research is purposed to analyze the student’s perception about the online teaching and learning process held in STIKes Pasapua of Ambon. This research has done by spreading a kind of questionnaire to be filled by all of the students who attend those processes. There are several platforms which are used in STIKes Pasapua as a tool to hold the online teaching process. They are zoom meeting, google meeting, google classroom and whatsapp. This online learning method has its own weakness. It needs more resources to access the internet and there are a lot of areas in Moluccas which do not reach by the internet. Another obstacle occurs within the subject with practice activity in laboratory or any other medical facilities. According to these weaknesses the online teaching and learning process should be reviewed to get the more effective results.